МУСТАҚИЛЛИК ЙИЛЛАРИДА ТАЪЛИМ ИСЛОҲОТЛАРИ: МУАММОЛАР ВА ТАЖРИБА (ТАРИХИЙ ТАҲЛИЛ) - Хатамов, Т.А. (SCIENCE and SOCIETY, 2020)
The article from a historical and scientific points of view analyzes the problems and reforms, as well as the concrete measures implemented to solve them in the public education system of Uzbekistan in the framework of the state National program for the development of school education in 2004–2009.